Dominica : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
Dominica has faced two major challenges during the past two decades: weak competitiveness and low potential growth. In addition to these economic challenges, the country has been facing frequent natural disasters. Growth is expected to pick up gradually. The financial system is highly liquid but monetary conditions have not eased. The external position is improving on strong service receipts. Fiscal policy is reaching its limit in terms of its ability to support economic activity. The balance of risks to the fiscal outlook is broadly balanced.